Establishing and Applying an International Market Selection Framework for Digital Multi-Sided Platforms Finding Suitable Countries for Forza’s Market Expansion - Forsberg, Olle; Wramdemark, Viktor (My University, 2023)
The purpose of this research paper is to establish a guiding framework for digi- tal multi-sided platform’s international market selection and utilize it to identify the optimal market(s) for Forza. Forza, an app that offers live scoring services for football, is a digital MSP that serves as the representative case in this case study. To begin with, a comprehensive literature review was conducted to develop a framework specifically tailored to digital MSPs. This process yielded a three-step approach for market selection. The first step involves an initial screening of poten- tial markets, followed by an evaluation of market size in the second step. Lastly, the third step considers the factors demographics, political, competition and strategic fit. Following the literature review, the framework was enhanced based on insights obtained from interviews conducted with representatives from Forza. This refine- ment resulted in a modified four-step approach. Notably, competition was shifted to the fourth and final step of the process. Additionally, the concept of strategic fit transformed from being treated as an independent factor to being seamlessly inte- grated as a comprehensive consideration across multiple factors. The key findings pertain to the unique aspects of international market selection for digital MSPs. Firstly, conducting a comprehensive analysis from multiple perspectives is crucial, given that an MSP serves multiple user groups. Secondly, a significant revelation is the shift in the treatment of strategic fit. Rather than being viewed as an im- portant yet separate factor, it is now examined and integrated thoroughly across the entire framework. When the established framework was utilized for the case of Forza, it was determined that Brazil emerged as the top recommendation for opti- mal market, followed by Nigeria, South Africa, and Ghana. Additionally, Vietnam, Chile, and Belgium hold potential as intriguing opportunities, contingent upon the identification of alternative revenue sources in these markets
Keywords: international market selection; market expansion; digital multi-sided platforms